Punctuation system in the 17th century London, Wellcome Library, MS. 3771. - Linehan Gómez, Sinéad (My University, 2022)
Medieval manuscripts were mostly designed to be read aloud, constructing the punctuation system to preserve the ‘reader’s breath’; not giving much consideration to the grammatical construction of the work (Hector 1958, 45). Even though the punctuation displayed in the medieval book varies substantially from the modern punctuation system, the medieval symbols coincide in appearance with the contemporary elements (Clemens & Graham 2007, 82). Nevertheless, with the introduction of the printing system in the Renaissance period, the printers provided order to the chaotic punctuation system. Printing favoured the development of standardisation, ‘but its own system did not entirely conform to modern usage, and, in any case, manuscripts generally employed much lighter and less consistent punctuation than printed books’ (Petti 1977, 25). This paper is concerned with the 17th-century English remedy book housed in London, Wellcome Library, MS. 3771, written by Doctor William Parnell (1685). MS. 3771 displays a collection of medical recipes arranged in an alphabetical distribution (chronologically displaying the prescriptions, that are enumerated within each letter), and, for the purpose, it makes use of different punctuation symbols for the expression of the different grammatical and rhetorical needs, such as the period, comma, colon, semicolon, virgule, and line-fillers, among others. In view of this, the paper describes the deployment of punctuation marks in MS. 3771 examining the punctuation system used by Dr. Parnell of MS. 3771 to shed light on the use and function of these marks and determine if there is any conventional system in his writing.
Keywords: Inglés - Ortografía - S. XVII; Puntuaction; Semicolon; Virgule; Caret